2013
DOI: 10.1175/jhm-d-12-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Reflectivity in the Presence of Partial Beam Blockage over a Mountainous Region Using X-Band Dual Polarization Radar

Abstract: Two approaches to correcting the partial beam blockage of radar reflectivity in mountainous areas were evaluated using X-band dual polarization radar data from the Hakone mountain region, Kanto, Japan. The comparatively simple digital elevation model (DEM) method calculates the power loss in the received signal based on the geometrical relationship between radar beams and a DEM. The second approach, the modified DEM method, attempts to account for unknown power losses related to ground clutter, hardware calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…et al, 2013). However, radar estimates of rainfall using Z H in areas of beam blockage are clearly biased in comparison with the ground-truth data (Zrnic and Ryzhkov 1996;Vivekanandan et al, 1999;Kucera et al, 2004;Krajewski et al, 2006;Friedrich et al, 2007;Lang et al, 2009;P.C. et al 2013).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…et al, 2013). However, radar estimates of rainfall using Z H in areas of beam blockage are clearly biased in comparison with the ground-truth data (Zrnic and Ryzhkov 1996;Vivekanandan et al, 1999;Kucera et al, 2004;Krajewski et al, 2006;Friedrich et al, 2007;Lang et al, 2009;P.C. et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Z H is a widely used parameter to estimate rainfall rate; many studies have used it to generate models that closely follow ground-truth data, especially for light to moderate rain Kim and Maki, 2012;P.C. et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that these high-resolution X-band weather radars can fill gaps in nationwide networks or be used for further investigating areas of special interest, e.g. mountainous regions (Beck and Bousquet, 2013;Shakti et al, 2013; Figuras i Ventura, J., Tabary P., 2013), urban areas (Berenguer et al, 2012;Chen and Chandrasekar, 2012;van de Beek, C. Z. et al, 2013), airports (Turso et al, 2009 or regions prone to floods (Matrosov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%